Local and systemic defence signalling in plants - Gaupels, Frank; Justus Liebig University Giessen (My University, 2015)
Signalling during induced defence responses of plants to biotic and abiotic stresses is often multi-layered and rather complex. By developing signal networks the plant maintains high flexibility, which is necessary for adequate reactions to ever-changing environmental conditions and a multitude of different pathogens. Redox signalling is a good example of how a seemingly rather simple set of signalling components can result in high complexity. Starting from O2-, NO and some redox enzymes chemical reactions between both radicals and interactions of the reactive intermediates with redox enzymes can result in an extreme versatility of possible messenger molecules. Protein S-nitrosylation is only one mechanism of signal transduction by NO. The significance of this protein modification in plant defence responses, particularly in the HR-PCD is well established and functions of some NO target proteins were already successfully characterized. However, the involvement of ONOO-,NO2 and protein nitration in defence signalling is just starting to be investigated.ROS and NO derivatives such as GSNO can move from the initial site of stress encounter to distal plant parts, thereby participating in the induction of systemic stress immunity. In this context it is important that the phloem can synthesize NO and might be the transport route for a rapid ROS-calcium-NO autopropagation wave. In this signal interaction NO might facilitate ROS accumulation by inhibiting antioxidant enzymes as it has been observed during the HR-PCD. H2O2, in turn, was shown to be a potent inducer of NO production in the phloem (Figure 4A). Perhaps the intensity of the initial stimulus decides if local amplification turns into systemic propagation of redox signalling.Similar apparent translocation velocities suggest also a link between rapid redox signalling and electrical signals. Such amplification loops currently emerge as a widespread phenomenon in systemic defence signalling.Particularly, the reactive molecules H2O2 and NO would be lost during long-distance transport due to dilution and scavenging and, for this reason, must be constantly synthesized en route. In general, systemic signal propagation waves can move cell-to-cell in all tissues but are most efficiently transmitted in the vasculature, particularly in the phloem. Communication between distal plant parts often involves sequential and parallel signalling events. For instance, systemic wound responses are regulated by electrical signals, ROS wave and JA. By flexibly combining partly independent signalling pathways the plant might optimize both speed as well as specificity of the defence response. Future research will have the challenging task of defining the molecular basis of signal interactions within the phloem.An intact and functional phloem is essential for plant performance and survival. Therefore, it is also of agronomical importance to analyse in detail inducible defence mechanisms of the phloem. A pioneering proteomic and metabolomic investigation of phloem wound responses has revealed some interesting wound-regulated phloem proteins including PP2 and CYP18. Both proteins were detected in phloem exudates from a number of different plant species including barley, rice, potato, castor bean and others. Therefore, studying the functions of PP2 and Cyp18 and increasing protein levels by breeding or biotechnological approaches could be a reasonable strategy for improving crop resistance to herbivorous and phloem-sucking insects, which cause major yield losses all over the world.
Pflanzliche Signalübertragung während lokaler und systemischer Abwehrreaktionen
Keywords: Abwehr; systemisch; Stickstoffmonoxid; NO; Phloem; defence; systemic; nitric oxide; NO; phloem; ddc:570